If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 18 = -4x + 34 Reorder the terms: 18 + -2x = -4x + 34 Reorder the terms: 18 + -2x = 34 + -4x Solving 18 + -2x = 34 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 18 + -2x + 4x = 34 + -4x + 4x Combine like terms: -2x + 4x = 2x 18 + 2x = 34 + -4x + 4x Combine like terms: -4x + 4x = 0 18 + 2x = 34 + 0 18 + 2x = 34 Add '-18' to each side of the equation. 18 + -18 + 2x = 34 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = 34 + -18 2x = 34 + -18 Combine like terms: 34 + -18 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 27/(-9) | | -9x+22+11x+21=2 | | 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 | | -6=-2/3y | | 3x+18=-3x-6 | | 6n+11-8n=22 | | X^3-1/X^3=14 | | 7=8(x+5)+5 | | 3.4a=7.004 | | 1=1/3x^2 | | 5(11-3x)+4(2x+1)=3 | | 7(x+4)-(3x-1)=8 | | (3x+4)=5x | | y=ctg(1-2x) | | y=ctg(1-2xz) | | 2+2+3=3 | | (12x+20)+(7x)+(20x-35)=180 | | 6=6(x+5)-2x | | (3x+7)=(5x-3) | | 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 | | (y-2)-(y+1)=(y-3)-2 | | y=arcsen(3x) | | -(2x+5)=-21 | | 5/8m=60 | | 7-6/5x=8 |